Visual mate choice in poison frogs. - Summers, Kyle; Symula, Rebecca; Clough, Mark E.; Cronin, Thomas (East Carolina University, 1999)
We investigated female mate choice on the basis of visual cues in two populations of Dendrobates pumilio, the strawberry poison frog, from the Bocas del Toro Archipelago in Panama, Central America. Mate choice experiments were carried out by presenting subject females of each of two morphs of this species (orange and green) from two different island populations (Nancy Key and Pope Island) with object frogs (one of each morph) under glass at one end of a terrarium. Recorded calls were played simultaneously from behind both object frogs. The experiments were carried out under two light regimes: (i) white light, and (ii) relatively monochromatic filtered blue light. Subject females from each population displayed a significant preference for their own morph under white light, but not under blue light. These results indicate that female D. pumilio use visual cues in mate choice, and suggest that colour may be the visual cue they use. Originally published Proc Biol Sci, Vol. 266, No. 1434, Nov. 1999
Keywords: Poison frogs; Dendrobatidae; Color; Visual; Mate choice